Need Analysis for the Development of Teaching Materials Using Task-Based Instruction for Nursing Students - Risman Wanci; Sujariati Sujariati; Maulina Maulina; Muhaimin Abdullah (Journal of Innovation in Educational and Cultural Research, 2024)
Providing appropriate teaching material is important because many students require exceptional teaching in specific fields. As an English lecturer, paying particular attention to students' learning needs is essential. This paper aims to analyze the English learning needs of nursing students. The research method applied in this paper was survey research. The results show that the respondents liked to learn English for nursing; all language skills were considered important, but speaking was chosen as a priority; in addition to classroom study, it is also essential to study outside class; one of the aims of learning English for nursing was to share information; all the learning methods provided were important, but study that focused on listening and pronunciation, reading while taking notes, repetition, and extensive group work were categorized as priorities; mostly the graduates said that English abilities are essential in the workplace for nurses; English abilities definitely support their jobs, and the teaching topics should be related to nursing. In conclusion, most respondents agreed with the plan to develop English teaching materials for nursing students based on task-based instruction. It is hoped that the results of this research can contribute positively to English lecturers and nursing students.